Neural Network Classifiers For Mongolian Character Recognition - Batsaikhan, Osorkhuu (2003)
In this research, we investigate Neural Network techniques, namely, Multilayer Perceptron (MLP) and Support vector Machines (SVMs0 for Mongolian character recognition.